2021
DOI: 10.1038/s41598-020-79658-4
|View full text |Cite
|
Sign up to set email alerts
|

Induced changes of pyrolysis temperature on the physicochemical traits of sewage sludge and on the potential ecological risks

Abstract: Biochar from sewage sludge is a low-cost sorbent that may be used for several environmental functions. This study evaluates the induced effects of pyrolysis temperature on the physicochemical characteristics of sewage sludge (SS) biochar produced at 350 (SSB350), 450 (SSB450) and 600 (SSB600), based on the metal enrichment index, metal mobility index (MMI), and potential ecological risk index (PERI) of Cd, Cu, Pb, and Zn. Increased pyrolysis temperature reduced the biochar concentration of elements that are lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 75 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Typically, activated carbon can be synthesized from a variety of carbonaceous materials including cherry stone [ 4 ], sugar cane bagasse [ 5 ], palm stone [ 6 ], agricultural waste [ 7 ], hemp stem hemicellulose [ 8 ], and bamboo [ 9 , 10 ] or coal [ 11 ], lignite [ 12 ], and peat [ 13 ]. Sewage sludge, the residual material produced as a by-product from sewage treatment plants and which contains large amounts of organic matter, could be another potential source for activated carbon production, since the biochar produced from the sewage sludge showed a reasonably high carbon content and surface area of 47% and 152 m 2 /g, respectively [ 14 , 15 ]. The elementary structures of activated carbon are graphene layers and quasi-graphitic fragments that are composed together, which are referred to as microcrystalline structures.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, activated carbon can be synthesized from a variety of carbonaceous materials including cherry stone [ 4 ], sugar cane bagasse [ 5 ], palm stone [ 6 ], agricultural waste [ 7 ], hemp stem hemicellulose [ 8 ], and bamboo [ 9 , 10 ] or coal [ 11 ], lignite [ 12 ], and peat [ 13 ]. Sewage sludge, the residual material produced as a by-product from sewage treatment plants and which contains large amounts of organic matter, could be another potential source for activated carbon production, since the biochar produced from the sewage sludge showed a reasonably high carbon content and surface area of 47% and 152 m 2 /g, respectively [ 14 , 15 ]. The elementary structures of activated carbon are graphene layers and quasi-graphitic fragments that are composed together, which are referred to as microcrystalline structures.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the yield, surface area, and pore structure was known to improve with the inherent minerals present in the sludge samples due to the improvements in metal catalyzed thermochemical reactions during pyrolysis [ 28 ]. Furthermore, another study concluded that the increase in pyrolysis temperature is known to increase surface area and stabilize the toxic metals present hence reducing the likelihood of leaching [ 29 ]. Hence, the produced char is considered low risk for the environment due to less bioavailability and decreased leaching capacity [ 30 ].…”
Section: Co-pyrolysis and Potential Chars For Water Treatmentmentioning
confidence: 99%
“…When oxygen was limited during the 600 • C heat treatment, N leaching was eliminated entirely. Oxygen limitation likely sequestered N via formation of biochar, volatilizing N compounds, and forming stable aromatic compounds [51].…”
Section: Nitrogen Desorptionmentioning
confidence: 99%